URGENSI DIAGNOSIS DALAM MENGATASI KESULITAN BELAJAR - Sattu Alang (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
Diagnose learning difficulties is quite heavy work. To perform a diagnosis must first know the cause of the difficulty of learning itself, only then will the diagnosis by looking at the symptoms that appear of self-learners who interpret that he was having trouble learning. After seeing the symptoms appear, diagnostic steps taken by the teachers, among others, the following: Conduct classroom observation to see the deviant behavior of students when following the lessons, check vision and hearing students in particular are alleged to have difficulty belajar.Mewawancarai parent or guardian students to know the happenings of the family who may pose difficulties belajar.Memberikan field diagnostic tests specific skills for mengetehui nature of learning difficulties experienced siswa.Memberikan test the ability of intelligence (IQ), especially to students who have learning difficulties. Efforts to overcome the difficulties of learning for the sake of improvement of learning, including analyzing the phenomenon displayed by learners, identify and define areas of specific skills that need improvement, preparing improvement program, in particular remedial teaching program (improvement of learning), and finally implement the program improvement. Diagnosis of learning difficulties is very important, because with positive actions on the improvement of learning is required.